2016
DOI: 10.1021/acs.cgd.6b00076
|View full text |Cite
|
Sign up to set email alerts
|

Modulator Effects on the Water-Based Synthesis of Zr/Hf Metal–Organic Frameworks: Quantitative Relationship Studies between Modulator, Synthetic Condition, and Performance

Abstract: The modulated synthesis of metal−organic frameworks (MOFs) remains empirical and challenging. Modulators are often applied and assumed capable of facilitating crystal growth by adjusting the reaction kinetics. However, most of the current studies are based on qualitative analysis and performance-leading synthesis, while no quantitative insights between modulator feature and MOF performance have been offered. In this work, we carried out a comprehensive study of the effects of three modulators (acetic acid, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
115
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 59 publications
(105 reference statements)
8
115
1
Order By: Relevance
“…31,37 In our previous study, we have demonstrated that the synthetic condition can play a determining role in the quality of resultant MOFs, which cannot be solely evaluated by powder x-ray diffraction (PXRD). 38 Herein, we report the optimal synthesis of this MOF with superb quality. By carrying out systematic studies via previously developed MHT approach, we found that highly crystalline (Supporting Information Figure S2) and octahedral shaped opt-UiO-66(Zr)-(OH) 2 nanocrystals ($100 nm, Figure 1d & Supporting Information Figure S2) could be easily obtained using an optimal molar ratio (105) of acetic acid (AA) to DOBDC in aqueous solutions with ZrOCl 2 Á8H 2 O as the metal source.…”
Section: Resultsmentioning
confidence: 99%
“…31,37 In our previous study, we have demonstrated that the synthetic condition can play a determining role in the quality of resultant MOFs, which cannot be solely evaluated by powder x-ray diffraction (PXRD). 38 Herein, we report the optimal synthesis of this MOF with superb quality. By carrying out systematic studies via previously developed MHT approach, we found that highly crystalline (Supporting Information Figure S2) and octahedral shaped opt-UiO-66(Zr)-(OH) 2 nanocrystals ($100 nm, Figure 1d & Supporting Information Figure S2) could be easily obtained using an optimal molar ratio (105) of acetic acid (AA) to DOBDC in aqueous solutions with ZrOCl 2 Á8H 2 O as the metal source.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of Hf‐UiO‐66‐Fum has been previously reported using water as the solvent . In combination with different modulators only products containing linker defects were obtained . As shown in our investigation, the use of a solvent mixture composed of DMF and HCOOH and a threefold excess of linker leads to the defect‐free Hf‐UiO‐66‐Fum.…”
Section: Resultsmentioning
confidence: 53%
“…The synthesis of Hf‐UiO‐66‐Fum has been previously reported using water as the solvent . In combination with different modulators only products containing linker defects were obtained .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations